2015
DOI: 10.5195/mitrip.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

Training Dietitians in Motivational Interviewing: A Pilot Study of the Effects on Dietitian and Patient Behaviour

Abstract: Objective: To evaluate the transfer of Motivational Interviewing (MI) skills to dietietic practice in a clinical setting, and the effect of this on patient behaviour.This involved a replication of Britt and Balmpied (2010), except with dietitians providing the MI rather than nurses educators as in the earlier study. The current study, therefore, is a both a test of replication and generalisation. Method: Two dietitians were trained in MI and effects of this training were evaluated on both practitioner and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Analysis of recordings of consultations demonstrated impacts in terms of behaviour and results with dietitians adopting more motivational interviewing consistent behaviours after training, while patients of dietitians who had received motivational interviewing training had significantly reduced saturated fat intakes compared to those of control dietitians but with no differences between groups for other diabetes‐related risk factors 53 . A pilot study evaluated the effect of a motivational interviewing training (workshop, ongoing coaching) completed by two dietitians and found that dietitians engaged in more motivational interviewing‐consistent behaviour after training, with corresponding changes in patient behaviour 52 . A study in the UK investigating the effect of motivational interviewing training on counselling behaviour, delivered to 32 student nutritionists as five 3‐h sessions and video feedback, reported that students used fewer closed questions and slightly more open questions post‐training 58 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of recordings of consultations demonstrated impacts in terms of behaviour and results with dietitians adopting more motivational interviewing consistent behaviours after training, while patients of dietitians who had received motivational interviewing training had significantly reduced saturated fat intakes compared to those of control dietitians but with no differences between groups for other diabetes‐related risk factors 53 . A pilot study evaluated the effect of a motivational interviewing training (workshop, ongoing coaching) completed by two dietitians and found that dietitians engaged in more motivational interviewing‐consistent behaviour after training, with corresponding changes in patient behaviour 52 . A study in the UK investigating the effect of motivational interviewing training on counselling behaviour, delivered to 32 student nutritionists as five 3‐h sessions and video feedback, reported that students used fewer closed questions and slightly more open questions post‐training 58 .…”
Section: Resultsmentioning
confidence: 99%
“…53 A pilot study evaluated the effect of a motivational interviewing training (workshop, ongoing coaching) completed by two dietitians and found that dietitians engaged in more motivational interviewingconsistent behaviour after training, with corresponding changes in patient behaviour. 52 A study in the UK investigating the effect of motivational interviewing training on counselling behaviour, delivered to 32 student nutritionists as five 3-h sessions and video feedback, reported that students used fewer closed questions and slightly more open questions posttraining. 58 Similar results in adoption of counselling skills more consistent with motivational interviewing after training were also seen in two abstracts relating to student dietitians in the USA 54,57 and in a 1970s' study that described a 'helping skills' programme for student dietitians in the USA.…”
Section: Teaching Skills For Multicultural Communicationmentioning
confidence: 99%
“…The positive effects of teaching MI have been demonstrated in numerous areas. Medical students demonstrated improved student confidence, increased knowledge of counseling techniques, and stronger belief in the importance of behavior change, and MI has helped client–practitioner communications and increased clients’ lifestyle changes (Britt & Blampied, 2010, 2015; Brown & Oriel, 1998; Poirier et al, 2004; Söderlund, Madson, Rubak, & Nilsen, 2011). The method used to train impacts MI effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…At least 15 million people have received MI treatment globally, and over 3,000 trainers have completed the training pathway to become MINT affiliated (Miller & Moyers, 2017;Miller & Rollnick, 2009). This addiction (e.g., Baer et al, 2004), mental health (e.g., Schoener, Madeja, Henderson, Ondersmaa, & Janisse, 2006), dietetics (e.g., Britt & Blampied, 2014), smoking cessation (e.g., Hayes et al, 2011), general practice (e.g., Rubak, Sandbaek, Lauritzen, Borch-Johnsen, & Christensen, 2006), juvenile corrections (e.g., Doran, Hohman, & Koutsenok, 2013), physical activity and lifestyle change (e.g., O'Halloran et al, 2014;Scott, Breckon, Copeland, & Hutchison, 2015). Recently, researchers have begun exploring the process and outcomes of training undergraduate students in MI from disciplines including nutrition, physiotherapy and occupational therapy (e.g., Fortune, Breckon, Norris, Eva, & Frater, 2019;Simper, Breckon, & Kilner, 2017).…”
Section: Introductionmentioning
confidence: 99%